Mesenchymal stem cells-derived exosomes as a promising new approach for the treatment of infertility caused by polycystic ovary syndrome - Izadi, Mahin; Rezvani, Mohammad Ebrahim; Aliabadi, Ali; Karimi, Mahdieh; Aflatoonian, Behrouz (Frontiers in Pharmacology, 2022)
Polycystic ovary syndrome (PCOS) is a multifactorial metabolic and most common endocrine disorder that affects 4 -21% of women at reproductive age. Chronic low-grade inflammation and irregular apoptosis of granulosa cells play a crucial role in the pathogenesis of PCOS infertility. Mesenchymal stem cells (MSCs)-derived exosomes and extracellular vesicles (EVs) are lipid bilayer complexes that act as a means of intercellular transferring of proteins, lipids, DNA and diversity of RNA species. It seems that this nanoparticles have therapeutic effects on the PCOS ovary such as regulating immunity response, anti-inflammatory (local and systemic) and suppress of granulosa cells (GCs) apoptosis. Although there are few studies demonstrating the effects of exosomes on PCOS and their exact mechanisms is still unknown, in the present study we reviewed the available studies of the functions of MSC-derived exosome, EVs and secretome on apoptosis of granulosa cells and inflammation in the ovary. Therefore, the novel cell-free therapeutic approaches for PCOS were suggested in this study.